Income Insurance in the Beekeeping Sector - Nersisyan, Nerses («Տնտեսագետ» հրատ․)
In today’s over-saturated technological era, the latest approaches demand the application of tools aligned with the times, especially in critical sectors like agriculture. The slogan "For the benefit of all, for collective welfare" perfectly characterizes the current trends in the development of agricultural insurance. By utilizing financial and economic levers, incentives, tools, and methods for regulating insurance relations, which together form the economic component, each participant recognizes their economic interests and contributes to developing the agricultural insurance system. Simultaneously, the behavior of participants in insurance relations and the use of individual elements of the economic component are determined by the insurance legislation system. This article analyzes and presents the key indicators of one of the most important agricultural branches in the Republic of Armenia (RA): beekeeping. Considering the unique features of this sector and its special significance for the RA, based on international studies, an attempt has been made to present potential forecasts and the implementation of beekeeping insurance in the country. Like the entire agricultural sector, beekeeping in our country is not immune to various risks. Transitioning from cost insurance to income insurance and applying innovative approaches will enable farmers to create additional value, thereby stimulating the development of beekeeping and the entire agricultural sector in our country.
Keywords: Finance